2011
DOI: 10.2527/jas.2010-3416
|View full text |Cite
|
Sign up to set email alerts
|

Estimating feed efficiency: Evaluation of mathematical models to predict individual intakes of steers fed in group pens

Abstract: To evaluate feed efficiency using residual feed intake (RFI), it is necessary to measure and record daily feed intake for each animal. This can be accomplished by housing them in individual pens or by using sophisticated electronic feeders in group pens. All the available options are very expensive and very laborious; therefore, several researchers have developed methods to predict individual DMI of cattle fed in group pens. Three intake models were tested with a data set of 60 Angus × Hereford steers fed a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Dry matter intakes, within a study, were overestimated at lesser intakes and underestimated at greater intakes for OLS solutions to Cruz et al (2010) and MARC data for both intercept and 0-intercept models. Cruz et al (2011) reported a similar finding, albeit for pen-fed cattle. When comparing steers (Cruz et al [2010] and MARC) whose ADFI i (observed) was less than average with those with observed ADFI i greater than average, residuals differed from 0 (P < 0.001).…”
Section: Resultssupporting
confidence: 66%
“…Dry matter intakes, within a study, were overestimated at lesser intakes and underestimated at greater intakes for OLS solutions to Cruz et al (2010) and MARC data for both intercept and 0-intercept models. Cruz et al (2011) reported a similar finding, albeit for pen-fed cattle. When comparing steers (Cruz et al [2010] and MARC) whose ADFI i (observed) was less than average with those with observed ADFI i greater than average, residuals differed from 0 (P < 0.001).…”
Section: Resultssupporting
confidence: 66%
“…In this study, using acid insoluble ash as a marker, the absence of a relationship between RFI and total tract digestibility may be related to the nature of the diet offered, as the effect of level of feed intake on digestion is of less magnitude with forage-based diets than with concentrate-based diets (Chilliard et al, 1995). A number of studies where high concentrate diets were offered to cattle have found that diet digestibility was negatively correlated with RFI Nkrumah et al, 2006;McDonald et al, 2010), although some have found no relationship (Cruz et al, 2011). However, whether the association with digestion and RFI is an inherent efficiency or mainly related to a higher passage rate of digesta due to intake is unclear.…”
Section: Lawrence Kenny Earley and Mcgeementioning
confidence: 99%
“…Because mean BW and ADG usually does not explain all the variation in DMI, we would expect a phenotypic correlation between observed DMI and RFI (0.42 < r < 0.74; [ 15 , 50 ]). Some [ 51 ] have suggested that nutritional models cannot satisfactorily determine individual DMI and RFI of group-fed cattle. Others [ 16 ] have indicated strong correlations (r > 0.89) between RFI and predicted intake difference ( PID = observed DMI—DMR), suggesting that PID would be more capable to identify animals with low DMI and slow ADG as inefficient compared to RFI.…”
Section: Resultsmentioning
confidence: 99%